Desain Overlay Perkerasan Lentur Pada Jalan Joyoboyo Timur Kediri Dengan Metode Analisa Komponen - Ervan Adi Prasetyo; Yosef Cahyo Setianto Poernomo; Eko Siswanto; Mochammad Danara Indra Pradigta (Faculty of Engineering, Kadiri University, 2022)
Road pavement damage is an important thing to pay attention to. Improper planning, increasing traffic volume loads to lack of care and maintenance are factors that cause road damage. Road damage has an impact on the safety of road users. On the Joyoboyo East Kediri road, there are several roads that suffered significant damage. This study aims to design the repair of damage to the East Kediri Joyoboyo road. Repairs are carried out by adding a layer of pavement to the potholes. The component analysis method is used to determine the required pavement thickness. With the component analysis method, the design equivalent cross section will be calculated based on traffic data, as well as soil bearing capacity, regional factors and surface index. So that the pavement thickness index is obtained to determine the required pavement thickness. The result of this research is that the cross equivalent is 116.730, the regional factor value is 0.5 and the Surface Finish Index is 1.5. From the results of these calculations, Nomogram 5 was used and the Pavement Thickness Index value was 5.2. So that the required overlay thickness is 5 cm. These results can be used as a reference in repairing pavement damage on the Joyoboyo Timur Kediri road, so that it can support the safety of road users and facilitate transportation.